IKLAN ENAMEL DAN PENGGAMBARAN PERUBAHAN KOTA DI ZAMAN HINDIA BELANDA - Karina Rima Melati (Institut Seni Indonesia Yogyakarta, 2013)
Ads enamel is present as part of a media phenomenon in the world of advertisingcommunication made with a complex reproductive techniques and has a characteristic thatdistinguishes it from other advertising media. Factors affecting the visual content of the message inthe repertoire of developmental enamel advertising in Indonesia, developed along with the progressespecially in the areas of economy, as well as an attempt penetration with idioms - idioms to suit itstarget market.The next development was the emergence of new ideas in making an alternativeadvertisement-based enamel, such as the packaging of food products (packaging), ashtrays, trays ortrays, seat backrest, backrest calendar, memo backrest, clocks, thermometers and so giant thatcreated with an attractive design.Keywords: Ads enamel, Delineation change the city, Past the Dutch East Indies